How Childhood Obesity May Be Harming Your Child’s Vision: A Systematic Review of High Myopia in Obese Children and Adolescents: Oral Presentation - Observational Study - General practitioner - Ajeng Kartika,; Seruni Hanna Ardhia,; Marcelius Patria Prabaniswara,; Sarah Shabrina,; Rona Ali Badjrai, (Ophthalmologica Indonesiana, 2024)
AbstractIntroduction & Objectives : High myopia is a severe and progressive form of myopia that can result in blindness. The prevalenceof high myopia is rising globally, and obesity has been identified as a potential risk factor, particularly in children and adolescents. This review aims to evaluate complex interplay between obesity and myopia in the young population.Methods : A systematic literature review was conducted through PubMed, Embase, and Cochrane databases using relevant keywords. Abstract-only papers, case reports/series, and review studies were excluded, and only studies published in English between 2019 - 2023 were considered. The study selection process will be presented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram.Results : This review analyzed four studies that involved 1.326.898 participants aged between 5 to 19 years. The majority of the studies found a significant association between obesity and high myopia (p